Classical Bartter’s syndrome (type III) disease with normocalciuria in an Indian adult male: A case report - Krovvidi, Sahithi; Kammila, Gayatri; Korrapati, Rakesh; Mupparaju, Jaya Sai; Naraharasetty, Akhila (Indian Journal of Case Reports, 2025)
Bartter’s syndrome (BS), well known as salt-wasting nephropathy, is a rare genetic disorder characterized by renal defects in ion transport, leading to electrolyte imbalances such as hypokalemia, metabolic alkalosis, renal salt wasting, hypercalciuria, and increased renin-angiotensin-aldosterone system with low to normal blood pressure. This inherited disease is frequently seen in neonates and is unusual in adults. Among the five types of BS, type III, the Classic BS is normally evident in later life and is the result of mutations in the CLCNKB gene. The present case report describes a rare case of adult-onset BS type III in a 40-year-old man. Biochemical analysis revealed hypokalemia (K+ 2.0 mmoL/L) with renal potassium wasting, metabolic alkalosis (HCO3- 28.8 mmoL/L), hypochloremia (Cl- 86 mEq/L), normomagnesemia (Mg 2+ 2.29 mg/dL), and normocalciuria (Ca 2+187.2 mg/day). Our report highlights the variation in clinical characteristics and emphasizes the need for understanding genetic and biochemical analyses in suspected BS cases.